Community Perspectives on Communicating About Precision Medicine in an Alaska Native Tribal Health Care System - Woodbury, R. Brian; Beans, Julie A.; Wark, Kyle A.; Spicer, Paul; Hiratsuka, Vanessa Y. (Frontiers in Communication, 2020)
Background: Precision medicine seeks to better tailor medical care to the needs of individual patients, but there are challenges involved in communicating to patients, health care providers, and health system leaders about this novel and complex approach to research and clinical care. These challenges may be exacerbated for Alaska Native and American Indian (ANAI) people, whose experiences of unethical research practices have left some ANAI communities hesitant to engage in research that involves extensive data-sharing and diminished control over the terms of data management and who may have distinct, culturally-informed communication needs and preferences. There is need for communication research to support Tribal health organizations and ANAI people as they consider implementation of and participation in precision medicine. To address that need, this study characterizes the informational needs and communication preferences of patients, providers, and leaders at an Alaska Native Tribal health organization. Methods: We conducted 46 individual, semi-structured interviews to explore perspectives on precision medicine and related communication needs among patients, providers, and leaders of a tribal health organization. Analysis involved team-based coding to identify a priori and emergent themes, followed by identification and recoding of content relevant to precision medicine informational needs and communication preferences. Results: Patients, providers, and leaders were described as both sources and recipients of information about precision medicine. Information deemed essential for making decisions about whether to participate in or implement a precision medicine program included essential information about the clinical and research applications of precision medicine, benefits and risks, health system costs and impacts, and data management practices. Preferred communication channels included digital and nondigital informational materials, as well as in-person learning opportunities for individuals and groups. Participants also describe contextual factors and barriers that influenced the acceptability and effectiveness of approaches to health communication. Conclusion: Results can inform approaches to communicating information about precision medicine to stakeholders within Tribal and other health care systems considering implementation of precision medicine in clinical or research contexts.